2,2′-[o-Phenylenebis(methylenethio)]bis(pyridine N-oxide) - Zhang, Chao-Yan (International Union of Crystallography, 2009)
In the title compound, C(18)H(16)N(2)O(2)S(2), the benzene ring makes dihedral angles of 7.41 and 86.59° with the two outer pyridine N-oxygen rings. Two short intramolecular C—H⋯S contacts occur. The crystal packing is stabilized by C—H⋯O hydrogen bonds, C—H⋯π interactions and weak π–π staking interactions [centroid–centroid distance 3.7596 (7) Å].